ENERGY EFFICIENTCLUSTERINGIN HETEROGENEOUS WIRELESS SENSOR NETWORKSUSING DEGREE OF CONNECTIVITY - Sikandar, Ajay; Kumar, Sushil (International journal of computer networks & communications, 2015)
Cluster head election is a key technique used to reduce energy consumption and enhancing the throughput of wireless sensor networks. In this paper, a new energy efficient clustering (E2C) protocol for heterogeneous wireless sensor networks is proposed. Cluster head is electedbased on the predicted residual energy of sensors, optimal probability of a sensor to become a cluster head, and its degree of connectivity as the parameters. The probability threshold to compete for the role of cluster head is derived. The probability threshold has been extended for multi-levels energy heterogeneity in the network. The proposed E2C protocol is simulated in MATLAB. Results obtained in the simulationshowthat performance of the proposed E2Cprotocol is betterthan stable election protocol (SEP), and distributed energy efficient clustering (DEEC) protocol in terms of energy consumption, throughput, and network lifetime.